Iatrogenic Sinistral Hypertension Complicating Screening Colonoscopy - Oliver J. Ziff; A. M. James Shapiro (Case Reports in Surgery)
Colonoscopy is widely accepted as the gold-standard screening technique for detecting malignancies in the distal gastrointestinal tract in patients with symptoms suggestive of colon cancer. However, this procedure is not without risk, including colonic perforation. We report a patient who was managed conservatively after colonoscopy induced perforation. Eighteen months after appearing to make a full recovery, he presented with an upper gastrointestinal bleed. Oesophago-gastro-duodenoscopy (OGD) revealed large gastric fundal varices and computed tomography (CT) revealed splenic vein thrombosis. The ensuing left-sided (sinistral) hypertension explains the development of the fundal varices in the presence of normal liver function. At surgery, a persistent abscess cavity was identified and cultures from this site grew Streptococcus anginosus. Curative splenectomy was performed and the patient made a full recovery. We advocate more prompt operative intervention in selected cases of iatrogenic colonic perforation with primary repair to prevent late complications.